KOMBINASI ISOLASI PADA STORAGE TANK SEBAGAI PENYIMPAN PANAS APLIKASI PADA SOLAR WATER HEATER - Kurnia Devi Ariswanda; Arrad Ghani Safitra (PROSIDING SNAST, 2018)
Solar water heater is a new renewable energy that produces heat energy for everyday use. In solar water heater required a heat storage device called a storage tank. One of the innovations to reduce heat loss in storage tanks by providing a combination of isolation. The purpose of this study is to retain heat from water in storage tanks at specific time intervals and increase tank effectiveness in the presence of a combination of isolation. In this study, the storage tank consists of two layers of barrier material and two layers of insulation using materials from sand, soil, bricks, and pool-rocks with variations of pool rocks-sand, sand-pool rocks, pool rocks-bricks, bricks-pool rocks, pool rocks-soil, and soil-pool rocks.. The experimental data is collected when the water temperature conditions reach 45 ° C to 35 ° C. Data taken in this research is temperature change of each layer of storage tank, water entry temperature, and time needed to get heat loss in every hour. The analysis used transient heat transfer and thermal resistance method to determine the heat loss and effectiveness of storage tanks in each variation. From this research, the highest effectivity on soil-pool rocks 68% with total heat loss 2968,98 Watt from distributed energy 9322,12 Watt. As for the lowest effectiveness on the bricks-pool rocks variation of 45% with a total heat loss of 6013,84 Watt of distributed energy 10996,83 Watt.